Comparative Efficacy & Safety of Intralesional Verapamil versus Intralesional Triamcinolone Acetonide as First-Line Therapy for Treating Hypertrophic Scars & Keloids - Sarah Zaka, Wardah Rehmat, Sara Ishaq, Nadia Saman, Kashif Ali, Ijaz Hussain Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertrophic scars and keloids are challenging fibroproliferative disorders with high recurrence rates. Intralesional therapies like verapamil and triamcinolone acetonide are widely used, yet their comparative efficacy and safety as first-line treatments remain underexplored. Objective: To compare the efficacy & safety of Intra lesional Verapamil versus Intra lesional Triamcinolone Acetonide as first-line therapy in treatment of Hypertrophic scars and Keloids. Study Design & Setting: Randomized clinical trial conducted on patients attending OPD of Plastic and reconstructive department of Sheikh Zayed Medical College, Rahim Yar Khan August 2022 to July 2023. Methodology: Patients fulfilling inclusion criteria were selected through non probability purposive sampling. After randomization, the study participants were divided into 2 groups, A and B. Group A given Intra lesional Injection of Verapamil, 2.5 mg/ml every 4 weeks and in Group B, Intralesional Injection of Trimcinolone Acetonide at a dose of 40 mg/ml was given at 4 weeks interval. A total of 6 sessions were done or till the flattening of the scar. Follow up was done after 5 months or till the scar was flattened by calculating Vancouver scar scale. VSS of < 3 was taken as success of treatment. After data collection and analysis, frequencies & percentages were calculated. The success rate of treatment with Intra lesional Injection of verapamil was compared to Intra lesional Injection of Triamcinolone Acetonide, Chi square test and t-tests were used as test of significance for qualitative and quantitative variables respectively. Results: This study conducted on 60 patients showed that most patients having hypertrophic scars and keloids were between ages 12-55 years. 60% affected were males, 45% dark skinned, 55% gave history of burn as most prevalent because whereas most common site of scars was presternal in both the groups (40 and 36.6%). The success of treatment in Group A treated with Intra lesional Injection of Verapamil was 28% versus 72% in patient in Group B this difference was statistically significant. Clinical Implication: Identifying a more effective and safer first-line intralesional agent can significantly improve scar outcomes, reduce recurrence, and guide evidence-based clinical management of keloids and hypertrophic scars. Conclusion: Intra lesional Injection of Triamcinolone Acetonide has better efficacy and safety than Intra lesional Verapamil as 1st line therapy in treating hypertrophic scars and keloids. Keywords: Hypertrophic Scar, Keloid, Intra lesional, First-line therapy, Verapamil,